Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Tematik IPA SD - Maya Guita Mawar; Rusmawan Rusmawan; Kensi Jati Hananingrum (Universitas Muhammadiyah Magelang, 2023)
The purpose of this research is to improve thematic science learning outcomes using the problem-based learning model of fifth grade elementary school students. This research was conducted at Kanisius Totogan Elementary School involving 28 fifth grade students. The research method used was a class action research method using 2 cycles. Data collection techniques using tests and observations. The data obtained were then analyzed using quantitative and qualitative methods. The results of this study indicate that student learning outcomes increase in each cycle. The percentage of complete learning outcomes before the implementation of cycle 1 (pre-cycle) is 46.4% with an average value of 72.0. Then, there was an increase of 28.6% or at a percentage of 75% with an average value of 80.2 in cycle I and increased again in cycle 2 with a percentage of 85. 7% with an average value of 85.2. The percentage gain along with the average value shows a significant increase in the thematic science learning outcomes of class V SD Kanisius Totogan. Keywords: problem based learning, learning outcomes, thematic, science